2019
DOI: 10.1002/app.47931
|View full text |Cite
|
Sign up to set email alerts
|

Protein–polymer interaction: Transfer loading at interfacial region of PES‐based membrane and BSA

Abstract: The adsorption of proteins onto polymeric surfaces is encountered in many natural and industrial processes and is a prerequisite to their efficient identification, separation, and purification by methods such as chromatography, and filtration. Nevertheless, the exact nature of the adsorption mechanisms and interfacial interactions is not easy to identify for a given protein-polymer system. Here, we aim to document the adsorption mechanism of a protein-polymer system by investigating the adsorption as well as d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 92 publications
1
3
0
Order By: Relevance
“…For the small protein aprotinin (6.5 kDa), this would be 1.5–7.7 nmol for a membrane area of 0.5 cm 2 . This amount would be in the same molar range we observed for the much smaller cation Cu 2+ , even if the adsorption of proteins to PES membranes is far more complex . However, if very low concentrations of toxic metal ions like Cu 2+ in μg L –1 range (e.g.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…For the small protein aprotinin (6.5 kDa), this would be 1.5–7.7 nmol for a membrane area of 0.5 cm 2 . This amount would be in the same molar range we observed for the much smaller cation Cu 2+ , even if the adsorption of proteins to PES membranes is far more complex . However, if very low concentrations of toxic metal ions like Cu 2+ in μg L –1 range (e.g.…”
Section: Resultssupporting
confidence: 69%
“…This amount would be in the same molar range we observed for the much smaller cation Cu 2+ , even if the adsorption of proteins to PES membranes is far more complex. 53 However, if very low concentrations of toxic metal ions like Cu 2+ in μg L –1 range (e.g. up to 500 μg L –1 ) are of interest, the observed membrane retention may strongly bias the assessment of the environmental risk.…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption of protein on polymer has been widely reported [36][37][38][39][40][41] as summarized in Table 1. The protein adsorption mechanism mainly focuses on one or more of van der Waals (VDW), electrostatic and hydrophobic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…There was no direct correlation between the adsorption capacity of BSA and HSP, and the immobilized BSA was increased with increasing VDW component of surface tension. The comprehensive characterization of BSA on polyethersulfone (PES) surface was conducted by scanning electron microscope (SEM), attenuated total reflection-Fourier transform infrared (FTIR), contact angle, zeta potential [38]. Surface charge density measurement showed that the adsorption of BSA on PES was irreversible at pH > 4.7 due to the strong electrostatic interaction between BSA and PES.…”
Section: Introductionmentioning
confidence: 99%